Sanitation in Roman military hospitals - Belfiglio, Valentine John (International Journal Of Community Medicine And Public Health, 2017)
Background:Sanitation, hygiene and an awareness of contagious diseases are essential factors in the successful operation of all military hospitals. The ancient, Roman physicians were aware of these factors and addressed them in the structure and system that they developed for their military hospitals. Methods:This study was conducted within the parameters of system and structure analysis. Central to the analysis of hygiene and sanitation in military hospitals is the study of their structure and processes. Results:Hygiene and sanitation were regularly practiced in Roman military hospitals. Roman physicians took steps to reduce sepsis and separated sick and wounded soldiers to minimize the spread of contagious diseases. Conclusions:The Romans were the first army of antiquity to practice a significant level of hygiene and sanitation in their military hospitals. It is more likely than not, that Roman physicians knew through deductive reasoning that pathologic microorganisms existed.